The Technology Acceptance Model in use of Technologies for Contactless Process during the Covid-19 Pandemic - Ginting, Ina Veronika; Syifa Alawiyah (Politeknik Pariwisata NHI Bandung, 2021)
The purpose of this study was to measure passenger acceptance of Technologies for Contactless Process (TFCP) provided by the airport to prevent the spread of Covid-19 by adopting the Technology Acceptance Model (TAM). The study collected 220 questionnaires from passengers using TFCP and the data was analysed using Likert scale techniques by measuring Perceived ease of use and perceived usefulness. The results of the study significantly that passengers are willing to adapt using TFCP. This research contributes as the basis of a better strategy by airport managers managing TFCP by understanding the passenger experience. Keywords: TAM; TFCP; Perceived Usefulness and Ease of Use.